Online Medicine for Pregnant Women - Sharon Davidesko; David Segal; Roni Peleg (International Journal of Telemedicine and Applications)
Objective. To assess the use of cell phones and email as means of communication between pregnant women and their gynecologists and family physicians. Study Design. A cross-sectional study of pregnant women at routine followup. One hundred and twenty women participated in the study. Results. The mean age was 27.4 ± 3.4 years. One hundred nineteen women owned a cell phone and 114 (95%) had an email address. Seventy-two women (60%) had their gynecologist's cell phone number and 50 women (42%) had their family physician’s cell phone number. More women contacted their gynecologist via cell phone or email during pregnancy compared to their family physician (P=0.005 and 0.009, resp.). Most preferred to communicate with their physician via cell phone at predetermined times, but by email at any time during the day (P<0.0001). They would use cell phones for emergencies or unusual problems but preferred email for other matters (P<0.0001). Conclusions. Pregnant women in the Negev region do not have a preference between the use of cell phones or email for medical consultation with their gynecologist or family physician. The provision of the physician’s cell phone numbers or email address together with the provision of guidelines and resources could improve healthcare services.